Edukasi Efisiensi Penggunaan Bahan Bakar Fosil di SMPN 1 Kuantan Hilir Baserah Kabupaten Kuantan Singingi Provinsi Riau - Muhammad Ariyon; Ellyan Sastraningsih; Elizar Elizar; Utary Aurellia Verdo (PELANTAR PRESS, 2025)
For millions of years, fossil fuels have been the main source of energy for both industry and everyday households. However, over-reliance on these fuels has had many negative consequences for the environment and health. Knowledge about the environmental impacts resulting from the use of fossil fuels is very important, because society will feel the impacts both directly and indirectly from the activities of using fossil fuels. Especially in remote areas or inland areas where there is still a lack of information about the potential environmental impacts of the use of fossil fuels. Therefore, it is very necessary to provide education and counseling for the public from an early age so that they receive information and enlightenment about the importance of efficient use of fossil fuels to reduce the environmental impacts they cause. The targets of community service activities are students of SMPN 1 Kuantan Hilir, Baserah District, Kuantan Singingi Regency, Riau Province. By understanding the importance of fossil energy efficiency from an early age, it is hoped that the younger generation can become a generation that cares more about the environment and the future of the earth